Risk of Pneumonitis and Pneumonia Associated With Immune Checkpoint Inhibitors for Solid Tumors: A Systematic Review and Meta-Analysis - Su, Qiang; Zhu, Emily C.; Wu, Jing-bo; Li, Teng; Hou, Yan-li; Wang, Di-ya; Gao, Zu-hua (Frontiers in Immunology, 2019)
Background: We performed a systematic review and meta-analysis to evaluate the risk of pneumonitis and pneumonia associated with immune checkpoint inhibitors (ICIs) for solid tumors. Methods: The following keywords were used in searching the Embase and PubMed database: pneumonitis, pneumonia, and immune checkpoint inhibitors. The data was analyzed by using the R software and Metafor package. Results: Among 3436 studies, 23 randomized clinical trials (RCTs) met our selection criteria which included data from 12876 patients. Compared with chemotherapy, PD-1 inhibitors showed significant increase in grade 1-5 and grade 3-5 pneumonitis (RR, 5.17, 95% CI: 2.82-9.47, p<0.001; RR, 4.14, 95% CI: 1.82-9.42, p<0.001), but not in pneumonia. PD-L1 inhibitors showed significant increase in grade 1-5 pneumonitis and pneumonia (RR, 3.25, 95% CI: 1.61-6.57, p<0.001; RR, 2.11, 95% CI: 1.20-3.70, p<0.001). There was no significant difference in any grade pneumonitis and pneumonia in cytotoxic T lymphocyte-associated protein 4 (CTLA4) inhibitors subgroup. Programmed cell death protein 1 (PD-1) inhibitor (nivolumab and pembrolizumab) showed significant increase in grade 1-5 pneumonitis, but only pembrolizumab showed significant increase in grade 3-5 pneumonitis. (RR, 5.64 95% CI: 1.94-16.38, p<0.001). Compared with PD-1 inhibitor (nivolumab) or CTLA-4 inhibitor (ipilimumab) monotherapy, PD-1 inhibitor and CTLA-4 inhibitor (nivolumab plus ipilimumab) combination therapies showed significant increase in grade 1-5 and grade 3-5 pneumonitis (RR 3.47, 95%CI:1.76-6.83, p<0.001; RR 3.48, 95%CI:1.10-11.02, p<0.001) Conclusions: PD-1/ PD-L1 inhibitors treatment could increase the risk of all-grade pneumonitis. CTLA4 inhibitor ipilimumab treatment alone could not increase the risk of pneumonitis but could augment the risk of pneumonitis in PD-1/ PD-L1 inhibitor treated patients. There was no significant increase in the risk of pneumonia after either PD-1/PDL-1inhibitor or CTLA4 inhibitor treatment alone or in combination.